2015
DOI: 10.11648/j.ejpm.20150306.15
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Low Back Pain and Associated Risk Factors Among Adama Hospital Medical College Staff, Ethiopia

Abstract: Back ground: Low back pain (LBP) is one of the most common work-related health problems among hospital workers. Work-related activities such as twisting, bending, sustained posture, repeated movements are regarded as associated risk factors for low back pain. The aim of this study is to assess the prevalence and associated risk factors of Low Back Pain among hospital workers. Methodology: An institution based cross sectional survey design was conducted among employees in Adama Hospital Medical College (AHMC), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
19
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 15 publications
4
19
0
1
Order By: Relevance
“…Similar findings were obtained from Adama and Gonder, Ethiopia. 2,26 This finding is also consistent with the study findings reported from Turkey, Iran, Rwanda, Taiwan, Nepal, Korea and Malaysia. 8,10,17,24,[38][39][40] This might be due to the direct patient care activities which are physically demanding, and escalates the LBP with repetitive exposure to the physical and psychosocial hazards.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Similar findings were obtained from Adama and Gonder, Ethiopia. 2,26 This finding is also consistent with the study findings reported from Turkey, Iran, Rwanda, Taiwan, Nepal, Korea and Malaysia. 8,10,17,24,[38][39][40] This might be due to the direct patient care activities which are physically demanding, and escalates the LBP with repetitive exposure to the physical and psychosocial hazards.…”
Section: Discussionsupporting
confidence: 92%
“…Hence, it was 73−76% in Switzerland, 13 62% in Dutch, 14 33-86% in Italy, 15 65.8% in Turkey, 16 90.3% in South Korea, 17 78% in Nepal, 12 63.1% in Malaysia, 8 54.3% in Qatar, 9 48.4−74.2% in Saudi Arabia, 11,18,19 74.5% in Yemen, 20 73.5 −77.19% in Nigeria, 3,21,22 79.3% in Egypt, 23 78% in Rwanda, 24 57.7% in Tunisia, 25 and 45.8-60% in Ethiopia so far. 3,26,27 Nurse's experience of low back pain is related to the nature of their job and influenced by different factors. Literatures unveiled that socio-demographic factors such as age, being female, married, longer years of work experience were associated with LBP among nurses.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…(Greece) and Deksisa Abebe (Ethiopia). [2122] While the findings by Spyropoulos were similar to ours, Abebe found that age and gender were not risk factors for LBP. Their findings in the age category may have been due to the majority of their respondents being below 40 years (77%), going by the 40-year threshold in our study, above which we found age to be a risk factor.…”
Section: Discussionsupporting
confidence: 83%
“…It has been shown that LBP causes an estimated 21.7 million disability adjusted life years (DALYs) accounting for about one-third of all occupational disabilities [1]. The burden of LBP also entails a profound negative impact on the quality of life, productivity, and work performance [2–4]. Globally, there has been a plethora of research conducted on the prevalence and risk factors arousing LBP among healthcare workers, particularly nurses [510].…”
Section: Introductionmentioning
confidence: 99%